PERUBAHAN KRITERIA AWAL WAKTU SUBUH MUHAMMADIYAH - Rahnat, Rahnat Hidayat; Jayusman (UIN ALAUDDIN MAKASSAR, 2023)
This study describes the change in the criteria for the start of Fajr Muhammadiyah time, the criteria used so far are suspected of not having the latest empirical basis. The focus of this research is: Review of the Fiqh of Ikhtilāf on the Construction of Changes in the Initial Criteria for Muhammadiyah Dawn in Relation to the Development of Astronomy Studies in Indonesia? The conclusions of this study are: changes in the initial criteria for Fajr Muhammadiyah have a strong foundation, namely: the opinion of astronomy or astronomy scholars from the 4th century to the present, the determination of the time of dawn from various countries, and the Study of the Tarjih Assembly regarding dawn observations in Indonesia. This is a legal and scientific basis in studying changes in the initial criteria for Fajr. This became the basis for the initial study at Dawn in relation to the development of the study of Astronomy in Indonesia.